2017
DOI: 10.1109/tsp.2017.2706179
|View full text |Cite
|
Sign up to set email alerts
|

Channel Estimation and Performance Analysis of One-Bit Massive MIMO Systems

Abstract: This paper considers channel estimation and system performance for the uplink of a single-cell massive multiple-input multiple-output (MIMO) system. Each receive antenna of the base station (BS) is assumed to be equipped with a pair of onebit analog-to-digital converters (ADCs) to quantize the real and imaginary part of the received signal. We first propose an approach for channel estimation that is applicable for both flat and frequency-selective fading, based on the Bussgang decomposition that reformulates t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
526
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 488 publications
(547 citation statements)
references
References 38 publications
19
526
1
1
Order By: Relevance
“…In this study, we assume that b m can uniformly select its value between b low and b up ( b low ≤ b up ). Moreover, if all ADCs use the same resolution, it follows that Σ α = α I M , which is similar with A d = α d I M of Li et al(eq. 36)…”
Section: Systems Modelsupporting
confidence: 78%
See 2 more Smart Citations
“…In this study, we assume that b m can uniformly select its value between b low and b up ( b low ≤ b up ). Moreover, if all ADCs use the same resolution, it follows that Σ α = α I M , which is similar with A d = α d I M of Li et al(eq. 36)…”
Section: Systems Modelsupporting
confidence: 78%
“…23 Only using one-bit ADCs in massive MIMO systems, channel estimation and performance analysis were offered by some researchers. 24,25 For relaying networks with low-resolution ADCs, it is validated that the performance loss caused by low-resolution ADCs can be compensated with increasing the number of antennas in a logarithmical scaling law. 12 Assuming that low-resolution ADCs are equipped at the relay station, Dong et al 26 derived closed-form sum rate expressions for both perfect and imperfect CSI and showed that low-resolution ADCs only result in limited sum rate loss when the number of antennas at the BS and relay station is relatively large compared to the number of users.…”
Section: Prior Workmentioning
confidence: 96%
See 1 more Smart Citation
“…The 1-bit signal recovery problem is also considered in the uplink channel estimation problem. 28,29 In particular, in the work of Stöckle et al, 28 to address the direction of arrival estimation issue in massive MIMO system, an efficient complex-valued BIHT (CBIHT) algorithm was proposed. In the work of Li et al, 29 a linear minimum mean-square-error (LMMSE) channel estimator was proposed by rewriting the nonlinear 1-bit quantization using a linear expression.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 In particular, in the work of Stöckle et al, 28 to address the direction of arrival estimation issue in massive MIMO system, an efficient complex-valued BIHT (CBIHT) algorithm was proposed. In the work of Li et al, 29 a linear minimum mean-square-error (LMMSE) channel estimator was proposed by rewriting the nonlinear 1-bit quantization using a linear expression. However, the quantization-based channel estimation and feedback fails to consider the prior support information of sparse channel between the consecutive frames, where the channel support of the previous frame can be a good predictor for the CSIT estimation in current frame.…”
Section: Introductionmentioning
confidence: 99%